Effect of confounding factors on a phospho-flow assay of ribosomal S6 protein for therapeutic drug monitoring of the mTOR-inhibitor everolimus in heart transplanted patients. (2nd January 2017) - Dieterlen, Maja-Theresa; John, Katja; Haase, Susanne; Garbade, Jens; Tarnok, Attila; Mohr, Friedrich W.; Bittner, Hartmuth B.; Barten, Markus J.
Abstract: Context: Several assays of monitoring immune cell function have been developed to enhance therapeutic drug monitoring. Objective: An in vitro -validated whole-blood assay of phosphorylated ribosomal protein S6 (pS6RP) was evaluated for confounders to monitor the mTOR-inhibitor everolimus (ERL). Materials and methods: Whole blood samples from 87 heart transplant recipients were analyzed for pS6RP-expression in CD3-positive T-cells by phospho-flow analysis. Results: ERL blood concentration, laboratory parameters, co-medications, demographic and clinical data were reviewed. Conclusion: Evaluating the pS6RP-assay revealed that pS6RP is influenced by cyclosporine A (CsA) blood concentration, duration of ERL treatment, co-medication with thiazide diuretics and different metabolic parameters.